Overcoming Adverse Childhood Experiences Through Writing Autoethnography - Fionna Gracia; Eko Handayani; Winarini Wilman Dahlan Mansoer (Faculty of Psychology, Universitas Gadjah Mada, 2022)
A collaborative autoethnographic study was conducted to describe the authors’ experiences in an aempt to reconcile with Adverse Childhood Experiences (ACEs). The participants of this research are the author, together with her elder brother. Data were gathered from online personal diaries through blogger, digital journals, participants' memories and writings regarding ACEs, of which analyzed in the form of narrative themes. The result shows that changes could happen if a person reflects on themselves and find meanings through their experiences even though ACEs indeed had negative impacts in adulthood. Various meanings obtained through events wrien in autoethnography which then brings the author to the process of awareness, whilst enabling her to understand ACEs from different perspectives and build a new motivation to make efforts of overcoming the side effects of her past traumatic experiences. The research can provide insights for mental health professionals to help adults dealing with past trauma. Aside from that, autoethnography is part of therapeutic tools which are effective not just for the authors, but also the readers who faced the same struggles as the author, in this context, make peace with ACEs. This enhances the importance of doing the research, not only to benefit practitioners, but also for future readers who experienced ACEs itself.